1972
DOI: 10.1002/cne.901440304
|View full text |Cite
|
Sign up to set email alerts
|

The synaptic glomerulus and the intrinsic neuron in the dorsal lateral geniculate nucleus of the cat

Abstract: The morphological characteristics of Class 111, Golgi Type I1 neurons are analyzed in Golgi impregnations of the lateral geniculate nucleus (LGN) in the cat with special attention given to the complex dendritic appendages of these cells, the multilobed dendritic terminals. In addition, electron microscopic studies demonstrate the presence of presynaptic dendritic (ID) terminals as major components of synaptic glomeruli. Electron microscopic analysis of serial thin sections confirm the dendritic origin and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
170
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(189 citation statements)
references
References 41 publications
18
170
1
Order By: Relevance
“…Within a single contact made by an RG bouton, multiple synapses at a short distance from each other were frequently observed. Glial processes appeared not to intervene in these synapses, but they typically surrounded the RG axonal-dendritic terminal as a capsule of thin glia sheath forming a glomerulus (Famiglietti and Peters, 1972). The scale in digital images was calibrated by a grating replica (Ted Pella).…”
Section: Methodsmentioning
confidence: 99%
“…Within a single contact made by an RG bouton, multiple synapses at a short distance from each other were frequently observed. Glial processes appeared not to intervene in these synapses, but they typically surrounded the RG axonal-dendritic terminal as a capsule of thin glia sheath forming a glomerulus (Famiglietti and Peters, 1972). The scale in digital images was calibrated by a grating replica (Ted Pella).…”
Section: Methodsmentioning
confidence: 99%
“…Carandini and colleagues (Mante et al, 2008) showed that models incorporating simple RC circuits to mimic both luminance and contrast gain doubled the accuracy of spike prediction in the LGN. Sherman (2004) has suggested that the triadic glomerulus (convergence of retina, interneuron, and brainstem terminal; Szentagothai, 1963;Famiglietti and Peters, 1972) common in the A-layer of the cat is an implementation of a mechanism for contrast gain control. Sherman's (2004) speculation is based on the observation that the glomerulus contains excitatory inputs from the retina, disynaptic inhibition of that retinal input (feedforward inhibition, Figure 3A), and a metabotropic glutamate receptor (mGlu5) that closes a K + 'leak' channel, depolarizing the interneuron and increasing its GABA 'drip' onto the relay cell.…”
Section: Luminance/contrast Gain Controlmentioning
confidence: 99%
“…In the visual system, GABA-containing inhibitory interneurons in the dorsal lateral geniculate nucleus (dLGN) innervate thalamocortical relay neurons by classical axodendritic synapses (F1 terminals) and dendrodendritic synapses (F2 terminals) (Guillery, 1969;Ralston, 1971;Famiglietti and Peters, 1972;Hamos et al, 1985;Montero, 1986). F2 terminals are usually involved in "triadic" arrangements in which retinogeniculate fibers provide monosynaptic excitatory inputs onto the thalamocortical relay neuron dendrites as well as F2 terminals (see Fig.…”
Section: Introductionmentioning
confidence: 99%